The Moderating Effect Of Social Capital In Relation To Entrepreneurial Orientation And Firm Performance - Jalali, Alireza (2013)
The importance of entrepreneurial orientation (EO), resource-based view (RBV), network types of social capital (SC) and small and medium enterprises (SMEs) have become the main focus in the manufacturing environment. In view of the highly competitive manufacturing environment, the ability and reliability of small and medium enterprises (SMEs) is very important in order to achieve desired SMEs performance namely growthprofitability. In addition to that, literature argues that further research is required in the area of entrepreneurship and firm performance. In order to address this need, the study investigates 1. The relationship between EO and Manufacturing SMEs performance and 2. The moderating effect of intra- and extra-industry network in EO and manufacturing SMEs performance relationship. Quantitative method was done through survey. Instrumentation of data-gathering in quantitative method was done through questionnaires and its validity was measured by content validity. The population of this study was industrial SMEs in Tehran and Hamedan. Proportionate stratified random sampling was employed and out of 351 questionnaires sent out, only 150 questionnaires were returned, yielding a return rate of 25 percent. A model is hypothesized and analyzed by multiple regressions. The result implies that EO positively improved manufacturing SMEs performance.